Eficiência das gestões de resíduos sólidos urbanos dos municípios mineiros em 2021: um estudo apoiado na ferramenta análise envoltória de dados - Viviane Jin Hee Kim (2024)
Urban Solid Waste Management (USWM) is a challenge for municipal administrations due to the increase in its generation and the negative environmental impacts from inefficient and lowquality management. In Brazil and Minas Gerais, there is a legal support through solid waste Policies (in national and state level); however, the panoramas and data from the National Sanitation Information System (SNIS, in Portuguese) show an insufficient situation. Since it is a public interest to seek maximum efficiency in USWM, which are a complex system and depends on several factors working simultaneously, the necessity for develop efficiency studies for solid waste management is identified. Thus, the objective of this study is to investigate the efficiency of USWM in Minas Gerais municipalities in 2021, based on SNIS data and applying Data Envelopment Analysis (DEA). The study indicated that only 96 municipalities, out of the 633 cities studied, were classified as efficient, which was considered poor. However, the investigation allowed the identification that there were efficient municipalities that had many gaps in the services provided regarding USWM, such as the absence of selective collection and/or reverse logistics, inadequate management Plans and final disposal (dumpsites). Therefore, it was considered that the use of DEA alone, using the 12 variables selected from the SNIS and for the 633 municipalities, was insufficient, as it portrayed a panorama that was not consistent with reality. This may have been a result of the questionable quality of the SNIS data and/or the limitation of the tool's classic models. Thus, these points were considered as the biggest limitations of this research, with recommendations for future studies. Finally, it was clear that the municipalities of Minas Gerais are not in compliance with the laws, in the case of those with any initiative, these were limited to the recycling chain and dumpsites elimination. The results also indicated that the participation of intermunicipal consortia did not bring great benefits to the municipalities (in relation to efficiency scores) and that there is no region in the state where efficient municipalities prevailed. Despite the improvements observed over time, as data declaration to SNIS or those in municipal management quality, it is urgent for the state of Minas Gerais to implement measures that result in effective compliance with the Policies, as this would promote integrated and sustainable SW management, the transition to a circular economy and accomplish with sustainable development goals.